KINERJA KEUANGAN PERUSAHAAN KESEHATAN DI BEI SEBELUM, SELAMA, DAN SESUDAH PANDEMI COVID-19 - Victoria, Michelle; Lindrawati, Lindrawati; Susanto, Adi (Jurnal Aplikasi Akuntansi, 2025)
The COVID-19 pandemic has impacted various economic sectors, including healthcare. During the pandemic, there was a surge in demand for healthcare products, accompanied by challenges such as supply chain disruptions and rising operational costs. After the pandemic, the sector faced declining demand for the products and challenges in adapting business strategies. These impacts influenced financial performance. This research aims to analyze differences in the financial performance of healthcare companies listed on the Indonesia Stock Exchange before, during, and after the pandemic. Financial performance is analyzed using liquidity, activity, debt, and profitability ratios to provide a comprehensive overview of the pandemic's impact on the sector. This quantitative research using an event study the COVID-19 pandemic. Data analysis is conducted using Wilcoxon Signed Rank test. The results show no differences in financial performance for liquidity, activity, debt, and profitability (Net Profit Margin and Return on Equity). However, profitability (Return on Assets) shows differences between the periods before and during the pandemic, as well as during and after the pandemic. This is attributed to the surge in demand for healthcare products during the pandemic, which improved financial performance, particularly profitability ratios. However, after the pandemic, some financial performance indicators, such as net profit margin and debt ratio, declined, reflecting the healthcare sector's adjustments to post-pandemic market conditions.